Cultivation of Religious Character Values in Social Studies Learning : A Case Study at Islamic School in West Bandung Regency - Arnie Fajar; Jajang Hendar Hendrawan; Asmanah Asmanah (Jurnal Paedagogy, 2023)
This study aims to describe the pattern of inculcation of religious character values in Social Studies (IPS) learning at Islamic Madrasah Aliyah (MA) Cipeundeuy, West Bandung Regency. The research method used was descriptive qualitative with a case study approach, and the research subjects included social studies teachers, students, the assistant headmaster, and the headmaster. Interviews, observation, and documentation were used as tools. Data analysis was carried out in three stages: data reduction, presentation, and verification. The results of this study indicated that: 1) Social studies teachers had planned social studies learning that integrates religious character values at the beginning of the school year or the beginning of the semester, including the preparation of annual programs, semester programs, syllabi, and lesson plans; 2) Implementing inculcating religious character values in the learning process included preliminary, core, and closing activities. The values of a religious character were piety to the almighty God, gratitude, respect, and tolerance for other religions, living in harmony with followers of other religions, and protecting the surrounding environment; 3) The efforts made by the teacher were to carry out the habituation of behavior according to religious character values continuously, providing exemplary good / commendable behavior through various activities; 4) The cultivation of religious character values in the social studies learning process was implemented following the lesson plans prepared by the social studies teacher. Students showed good attitudes/commendable inside and outside the classroom.